Comparison of the structure and function of phospholamban and the arginine-14 deficient mutant associated with dilated cardiomyopathy. - Eleri Hughes; David A Middleton (PLoS ONE)
Phospholamban (PLB) is a pentameric protein that plays an important role in regulating cardiac contractility via a reversible inhibitory association with the sarcoplasmic reticulum Ca2+ATPase (SERCA), the enzyme responsible for maintaining correct calcium homeostasis. Here we study the functional and biophysical characteristics of a PLB mutant associated with human dilated cardiomyopathy (DCM), with a deletion of arginine at position 14 (PLBR14Δ). In agreement with recent findings, we find that PLBR14Δ has a reduced inhibitory effect on SERCA compared to wild type PLB (PLBWT) when reconstituted into lipid membranes. The mutation also leads to a large reduction in the protein kinase A-catalysed phosphorylation of Ser-16 in the cytoplasmic domain of PLBR14Δ. Measurements on SERCA co-reconstituted with an equimolar mixture of PLBWT and PLBR14Δ (representing the lethal heterozygous state associated with DCM) indicates that the loss-of-function mutation has a dominant effect on PLBWT functionality and phosphorylation capacity, suggesting that mixed PLBWT/PLBR14Δ pentamers are formed that have characteristics typical of the mutant protein. Structural and biophysical analysis of PLBR14Δ indicates that the mutation perturbs slightly the helical structure of the PLB cytoplasmic domain and reduces its affinity for the phospholipid bilayer surface, thereby altering the orientation of the cytoplasmic domain relative to the wild-type protein. These results indicate that the structure and function consequences of the R14 deletion have profound effects on the regulation of SERCA which may contribute to the aetiology of DCM.